The Overview of Optimization Methods Applied to Truss-Z Modular System - Zawidzki, Machi (Computer Assisted Methods in Engineering and Science; Vol 27 No 2-3 (2020), 2020)
Extremely Modular Systems (EMSs) are comprised of as few types of modules as possible and allow creating structurally sound free-form structures that are not constrained by a regular tessellation of space. Truss-Z is the first EMS introduced, and its purpose is to create free-form pedestrian ramps and ramp networks in any given environment. This paper presents an overview of various multi-objective optimization methods applied to Truss-Z structures.